Sujetos del deseo - Marambio, Soledad (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2021)
This book analyzes, conceptualizes and historicizes the amateur translator figure as political and cultural agent in US-Latin American relations, from the end of the 19th century to the mid-20th century. Centered on the work of two US-American translators, Alice Stone Blackwell and Isaac Goldberg, it is the first study to offer a modern history of the amateur translator as subject of resistance and cultural mediator between the two regions.